What is artificial meat and what does it mean for the future of the meat industry? - Sarah P F Bonny; Graham E Gardner; David W Pethick; Jean-François Hocquette (Journal of Integrative Agriculture, 2015)
The meat industry cannot respond to increases in demand by ever increasing resource use. The industry must find solutions to issues regarding animal welfare, health and sustainability and will have to do so in the face of competition from emerging non-traditional meat and protein products in an increasingly complex regulatory environment. These novel meat and protein products, otherwise known as ‘artificial meat’ are utilising ground breaking technologies designed to meet the issues facing the conventional meat industry. These artificial meats, in vitro or cultured meat and meat from genetically modified organisms have no real capacity to compete with conventional meat production in the present environment. However, meat replacements manufactured from plant proteins and mycoproteins are currently the biggest competitors and are gaining a small percentage of the market. Manufactured meats may push conventional meat into the premium end of the market, and supply the bulk, cheap end of the market if conventional meat products become more expensive and the palatability and versatility of manufactured meats improve. In time the technology for other artificial meats such as meat from genetic modified organisms or cultured meat may become sufficiently developed for these products to enter the market with no complexity of the competition between meat products. Conventional meat producers can assimilate agroecology ecology concepts in order to develop sustainable animal production systems. The conventional meat industry can also benefit from assimilating biotechnologies such as cloning and genetic modification technologies, using the technology to adapt to the changing environment and respond to the increasing competition from artificial meats. Although it will depend at least partly on the evolution of conventional meat production, the future of artificial meat produced from stem cells appears uncertain at this time.